Development of Thesaurus for Hindi - Kaur, Mandeep (International Journal of Computer Sciences and Engineering, 2019)
NLP is a vast field and thesaurus is its integral part. Thesaurus is a software tool which is inbuilt in few word processors that provides synonyms for selected words. A thesaurus is used on a computer while writing an e-mail, letter, or paper to find an alternative meaning for words. A thesaurus is a reference work that lists the synonyms and sometimes antonyms of words. Synonyms are words with similar meanings, and antonyms are words with opposite meanings. The research work in the paper elaborates the development of thesaurus in relevance with the Hindi language. The paper focuses on the development of framework which may assist the people finding it difficult to write and dealing with Hindi.